Let me be frank with you ebook A frank bascombe book. - Ford, Richard (Frank Bascombe, 2014)
A brilliant new work that returns Richard Ford to the hallowed territory that sealed his reputation as an American master: the world of Frank Bascombe, and the landscape of his celebrated novels The Sportswriter, the Pulitzer Prize and PEN/Faulkner winning Independence Day, and The Lay of the Land. In his trio of world-acclaimed novels portraying the life of an entire American generation, Richard Ford has imagined one of the most indelible and widely discussed characters in modern literature, Frank Bascombe. Through Bascombe—protean, funny, profane, wise, often inappropriate—we've witnessed the aspirations, sorrows, longings, achievements and failings of an American life in the twilight of the twentieth century. Now, in Let Me Be Frank with You, Ford reinvents Bascombe in the aftermath of Hurricane Sandy. In four richly luminous narratives, Bascombe (and Ford) attempts to reconcile, interpret and console a world undone by calamity. It is a moving and wondrous and extremely funny odyssey through the America we live in at this moment. Ford is here again working with the maturity and brilliance of a writer at the absolute height of his powers.